Pre-season total energy expenditure and dietary intake of professional male soccer players: A doubly labelled water study - Jenkinson, A.; Jones, B.; Chesson, L.; Wilson, L.; Price, R.; Hambly, C.; Speakman, J. R.; Costello, N. (European Journal of Sport Science, 2026)
Limited data exist describing how professional footballers meet their energy requirements during pre-season, a phase characterised by increased training volume and a progressive shift from general conditioning to football-specific preparation. This study quantified total, resting, and activity energy expenditure (AEE), diet-induced thermogenesis, water turnover, and dietary intake in six professional male soccer players (age: 25 ± 1 year; height: 182.5 ± 10.1 cm; body mass: 77.8 ± 8.2 kg). Players were studied across 14 consecutive days, representing training-only and training-plus-match microcycles. Total energy expenditure (TEE) was measured using doubly labelled water, resting energy expenditure (REE) by indirect calorimetry and dietary intake using the remote food photography method. Fourteen-day mean TEE, REE, AEE and water turnover were 13.25 ± 1.31 MJ·day-1, 7.96 ± 0.89 MJ·day-1, 4.20 ± 1.03 MJ·day-1, 5.16 ± 0.66 L·day-1, respectively. Physical activity level was 1.67 ± 0.16 AU. Energy, carbohydrate, protein, and fat intakes were 10.95 ± 1.52 MJ·day-1, 2.8 ± 0.6 g·kg-1·day-1, 2.2 ± 0.4 g·kg-1·day-1, and 1.5 ± 0.4 g·kg-1·day-1, respectively. Total energy expenditure was not significantly different between training-only and training-plus-match microcycles (+1.89 ± 1.98 MJ·day-1; ES = 0.95 ± 1.08; p = 0.100). No significant differences were observed in energy or macronutrient intake across weekly microcycles (p > 0.068) or between days (p > 0.144). Players did not achieve energy balance or align dietary intake with day-to-day training demands, suggesting limited nutrition periodisation during pre-season. These findings highlight the need for practitioners to implement strategies supporting fuelling, recovery and adaptation during this critical phase.